Quantifying the role of individual diabatic processes for the formation of PV anomalies in a North Pacific cyclone. (20th June 2019) - Attinger, Roman; Spreitzer, Elisa; Boettcher, Maxi; Forbes, Richard; Wernli, Heini; Joos, Hanna
Abstract : Processes that do not conserve potential vorticity (PV) have a profound impact on the intensity, evolution, and mesoscale details of extratropical weather systems. This study aims at quantifying and improving the understanding of how and when physical processes modify PV in cyclones. To this end, a 6‐day forecast of a North Pacific cyclone is performed using a recent operational version of the ECMWF global numerical weather prediction model. Hourly instantaneous temperature and momentum tendencies of each parametrized process are used to compute the corresponding PV tendencies. By integrating these diabatic PV rates along backward trajectories, the relative contribution of individual processes for the PV budget can be assessed. The cold front is characterized by an elongated filament of increased PV, generated by latent heating due to condensation at the front as well as long‐wave radiative cooling at the surface. Turbulent mixing at the interface of the boundary layer decreases PV behind the cold front during the early stage of the cyclone, while sublimation of snow produces negative PV in the mature phase. A broad region of enhanced PV is found along the warm front, generated by condensation and turbulence at the front as well as long‐wave radiative cooling at the surface. The region of decreased PV north of the warm front is mainly modified by snow melting and sublimation. Finally, high values of PV along the bent‐back front and the cyclone centre are generated by condensation, convection, snow melting and sublimation. In general, turbulent mixing offsets intense PV modification induced by the other processes. This study highlights the relevance of condensation, melting and sublimation of snow, long‐wave radiative cooling, turbulence, and convection for the production of low‐level PV anomalies and underlines the importance of correctly representing these processes in weather prediction models. Abstract : The modification of potential vorticity (PV) by diabatic processes is assessed in an IFS simulation of a North Pacific cyclone. Hourly temperature and momentum tendencies from every parametrized physical process are used to compute their respective PV rates and subsequently traced in a Lagrangian framework. Condensation, sublimation and melting of snow, long‐wave radiative cooling, convection, and turbulence all significantly affect PV along the fronts and in the cyclone centre. Turbulent mixing of temperature generally mitigates the influence exerted by the other processes.